PENDEKATAN PSYCHOTHERAPY AGAMA DALAM MENANGGULANGI PERILAKU MENYIMPANG (LGBT) - Dodi Pasilaputra (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2016)
Abstract LGBT deviant behavior is a behavior that arose as a result of the pressured experienced by individuals about the circumstances and changes of times that they can’t face in accordance to religious teachings. That individuals diseases can never be treated with any therapy device except go back to religious psychotherapy. Application of religious psychotherapy approaches aimed to; 1) strengthen the motivation, 2) reducing emotional stress, 3) developing the potential, 4) change the habits of maladaptive, 5) changing the cognitive structure, 6) increasing the capacity to make appropriate decisions, 7) increase self knowledge / insight, 8) improve personal relations, 9) transforms the process of somatic increased body awareness, and 10) develop awareness, control and creativity. Forms of religious psychotherapy approach in tackling LGBT deviant behavior such as; 1) set-up, approach by inviting individuals to neutralize subconscious psychological resistance (psychological reversal) ¸ and individuals are invited to express desires (willpower) to develop themselves, 2) tune in, arouse negative emotions of clients and then return it all to the result of negative emotions, and 3) tapping, opening and developing the client insight into the good expectations that can be done and achieved in the future. Keywords:. LGBT, psychotherapy, deviant behavior Abstrak Perilaku menyimpang dalam bentuk LGBT merupakan perilaku yang muncul sebagai akibat individu selalu merasa tertekan dengan keadaan dan perkembangan zaman yang tidak mampu ia sikapi sesuai dengan ajaran agama. Penyakit individu itu tidak akan pernah dapat diterapi dengan alat terapi apapun kecuali kembali kepada psychotherapy agama. Penerapan pendekatan psychotherapy agama bertujuan; 1) memperkuat motivasi, 2) mengurangi tekanan emosi, 3) mengembangkan potensi, 4) merubah kebiasaan maladaptif, 5) merubah struktur kognitif, 6) meningkatkan kapasitas untuk mengambil keputusan dengan tepat, 7) meningkatkan pengetahuan diri/insight, 8) meningkatkan hubungan pribadi, 9) merubah proses somatik meningkatkan kesadaran tubuh, dan 10) mengembangkan kesadaran, kontrol dan kreatifitas. Bentuk pendekatan psychotherapy agama dalam menanggulangi perilaku menyimpang LGBT di antaranya; 1) set-up, pendekatan dengan mengajak individu untuk menetralisir perlawanan psikologis bawah sadar (psychological reversal)¸ dan individu diajak untuk mengungkapkan keinginan (tekad)nya dalam mengembangkan diri, 2) tune in, membangkitkan emosi negatif klien dan kemudian mengembalikan semuanya kepada akibat dari emosi negatif tersebut, dan 3) tapping, membuka dan mengembangkan wawasan klien dengan harapan-harapan baik yang bisa dilakukan dan dicapainya pada masa yang akan datang. Kata Kunci: LGBT, Psikoterapi, Perilaku Menyimpang